Analisis Aspek Religiusitas Tokoh Utama dalam Novel Gadis Pantai Karya Pramoedya Ananta Toer (Tinjauan Sosiologi Sastra) - Setri Ayu Soleha; Wayan Satria Jaya; Andri Wicaksono (LPPM STKIP PGRI Bandar Lampung, 2020)
The purpose of this study is to describe the religious elements of the main character contained in the novel Gadis Pantai by Pramoedya Ananta Toer, as well as the social life of the community in the novel Gadis Pantai. The approach used in this research is a descriptive qualitative. The results showed that the main character, namely Pantai Girl, was described as someone who came from ordinary people who never worshiped so that they belonged to the abangan Islamic group, while the Bendoro figure was a priyayi santri figure with all his devotion to the religion he believed in, but behind his obedience Bendoro was a figure priyayi santri who likes to talk to their wives, are evil and rude. The social life of the community in Pramoedya Ananta toer's novel Gadis Pantai, the figure of bendoro represents the priyayi (aristocratic) group, while Gadis Pantai represents the common people. The difference between these groups has given an exact picture of the gap between the priyayi and the common people.